MUQADDIMAH IBNU KHALDUN: STUDY OF ISLAMIC HISTORIOGRAPHY: Islamic Historiography - Abd. Rahim, Ahmad Habib Akramullah; Susmihara,; Yani, Ahmad (Al-Hikmah, 2023)
The full name of an Ibn Khaldun is Abd al-Rahman bin Muhammad bin Mohammad bin Hasan bin Jabar bin Mohammad bin Ibrahim bin Abd al-Rahman bin Khaldun. Then he was born in the area of Tunisia, a region in North Africa, around 732 H or 1332 AD, he was a family of migrants from the Andalusian region, a region in Southern Spain, who now moved to the Tunisian area around the middle of the VII century H. The origin of a family The real Ibnu Khaldun was from the Hadramaut area, in the southern Yemen region. Ibnu Khaldun started his education at the age of 18 between 1332 and 1350 AD. As was the case with the Muslims at that time, Ibnu Khaldun's father was the first teacher figure who had taught him traditionally the basic values of Islam. During his stay in the Tunisian area until 751 H, Ibn Khaldun was very diligent in studying and reading and he attended the assembly of his teacher, Muhammad Ibrahim Al-Abili, every time. At that time, Ibnu Khaldun was already 20 years old. And at that time Ibn Khaldun was summoned by Abu Muhammad Ibn Tarafkin, one of the rulers who was in the Tunisian area, to assume the position of secretary to the ruler of Sultan Abu Ishaq Ibnu Abu Yahya Al-Hafsi. Ibnu Khaldun is one of the political activists and thinkers who was born in the Tunisa area in 1332 and he died in Egypt in 1406. Before he died he had spent much of his life in political struggles and adventures in various forms, at different times and at different times. the world in which he lives. Apart from being a political activist, he is also an expert thinker and is very observant of the knowledge he has and he is a very sharp analyst. He wrote down the results of his observations in a book consisting of several volumes on history, a book he called "Ibar" which is a book that is a role model that humans can take from history. The first part of the book he called "Muqaddimah", which means "Introduction". The works can be seen from the title Al-Ibar wa Diwan Al-Mubtada wa Al-Khabar fi, Ayyam Al-Arab wa al-Ajam wa Al-Barbar, wa Man Asharahum min Dzawi Al-Sulthan Al-Akbar, and consists of several volumes.